Persepsi Wisatawan Tentang 4 A di Kawasan Geostite Kaldera Danau Toba - Harpan, Jhodil Khoir; Butar-butar, Indi Andira; Sitompul, Johannes; Handara, Putra; Rajagukguk, Switno; Budi, Arfan Setia (Jurnal Akademi Pariwisata Medan, 2025)
This study aims to determine how tourists perceive the Lake Toba caldera regarding the 4 As (attractions, Accessibility, Facilities, and Supporting Services). As we know, Lake Toba, located in North Sumatra, has been recognized as a UNESCO Global Geopark due to its unique geology and cultural richness. This research used quantitative descriptive research, a type that describes variables as they are, supported by numerical data generated from real-world situations. The results of this study are used as a reference for developing sustainable tourism and improving the quality of the tourist experience. The results of this study indicate that tourists' views regarding the 4 As have both positive and negative results. The positive results are attractions and accessibility, while the negative results are based on the data obtained, namely facilities and supporting services. This research is expected to help address and improve the shortcomings of the Lake Toba caldera regarding the 4 As.